Arap edebiyatında Azdâd hakkında yazılan eserlerin karşılaştırmalı incelemesi - Avşar, Erkan (My University, 2003)
GENEL BILGILER Isim ve Soyadi: Erkan Avsar Anabilim Dali: Ilahiyat Programi: Arap Dili ve Belagati Tez Danismani: Prof. Dr. Ismail Durmus Tez Türü ve Tarihi: Yüksek Lisans – Eylül 2003 Azdad, Addad, Ezdad, Zit

ARAP EDEBIYATINDA AZDÂD HAKKINDA YAZILAN ESERLERIN KARSILASTIRMALI INCELEMESI Ezdâd (Azdâd), Arapçada ayni anda iki zit anlami birden ifade eden kelimelere verilen bir terimdir. Meselâ hem “siyah” hem de “beyaz” manasina kullanilan cevn ya da hem “büyük” hem de “küçük” manasina kullanilan celel kelimeleri gibi. Arap edebiyatinda azdâd (ezdâd) hakkinda yazilan kitaplarin karsilastirmali incelemesini yaptigimiz çalismamiz bir giris, üç bölüm ve bir ekten olusmaktadir. Giriste Arap Dili, bu dilde yapilan ilk gramer çalismalari, bu çalismalara bagli olarak olusan dil ekolleri, bu dildeki ilk sözlük çalismalari ve dilde genel hatlariyla ezdâd meselesini ele aldik. Birinci bölümde ezdâdin tanimi, varligi hakkindaki süpheler, tür ve çesitleri, tarihsel gelisimi gibi konulara degindik. Ikinci bölümde kitap, makale, yapilan çalismalar gibi ezdâdla alâkali kaynaklarin listesini verip her birini kisaca tanittik. Üçüncü bölümde ise ezdâd hakkinda yazilan kitaplarin karsilastirmali incelemesini yaptik. Ek kisminda ise en çok rastladigimiz ezdâd kelimeleri ve Türkçelerini bir lügatçe seklinde sunduk. Name and Surname: Erkan Avsar Field: Theology Program: Arabic Language and Eloquence Supervisor: Prof. Dr. Ismail Durmus Degree Awarded and Date: Master – September 2003 Key Words: Addad, Antonym Homophones ABSTRACT A COMPARATIVE TREATISE OF BOOKS WRITTEN ON ADDAD (ANTONYM HOMOPHONES) IN ARABIC LITERATURE Addad (Antonym Homophones), is a term given to words expressing two opposite meaning in the same word in Arabic. For example words such as cevn meaning both “white” and “black” or celel meaning both “big” and “small”. The study of a comparative treatise of books written on addad (antonym homophones) in Arabic Literature constitutes an introduction, three parts and an annex. In the introduction part, I have taken up the points of Arabic Language, first grammar studies in this language, language schools constituted depending on these studies, the first dictionary studies in this language and addad (antonym homophones) subject in general terms. In the first part, I have pointed out subjects such as the definition of addad (antonym homophones), doubts on the existence of the term, types and kinds of it, historical development. In the second part, I have listed resources related to addad (antonym homophones) such as books, articles and studies and introduced each of them briefly. In the third part, I have made a comparative treatise of books written on addad (antonym homophones). In the annex part, I have presented the most encountered addad (antonym homophones) words and their Turkish meanings as a glossary.
Keywords: Arap Edebiyatı; Arapça; Azdad; Dil